Manajemen Sitasi (Psikologi, Laktasi, Gizi): Monitoring Kesehatan Fisik Jiwa Ibu Menyusui di Masa Pandemi Covid 19 - Liyanovitasari, Liyanovitasari; Oktarina, Natalia Devi (UNIVERSITAS NGUDI WALUYO, 2022)
Transmission of Covid-19 during pregnancy or childbirth is still rare. Global guidelines released by WHO and Unicef believe that until now there is no evidence or case reports of vertical transmission from mother to fetus. In limited studies, there have been no findings of Covid-19 in breast milk in breastfeeding mothers who have been confirmed positive. These two reasons allow mothers with Covid-19 to continue breastfeeding and provide breast milk. Nowadays parents' anxiety increases with the problems of their income, food, and future. The success of breastfeeding will increase if the mother gets support from the family. This community service activity was carried out for 1 day on November 30, 2021, starting from the preparation stage, collecting data on breastfeeding mothers, providing materials, and evaluating. The material delivery stage, where breastfeeding mothers will receive